Transsexualism and hetrosexual matrix: a critical and empirical study of Judith Butler's performative theory of gender - Soley Beltran, Patricia (University of Edinburgh, 2001)
This thesis aims to clarify Judith Butler's performative theory of gender and to study the general processes of gender acquisition. Butler's notion of the body, her account of gender acquisition and her problematisation of the sex/gender distinction is widely misunderstood as being radically constructivist. However, the importance of her contribution to feminist debates on antiessentialism and the political value of the sex/gender distinction requires careful examination. Butlers attempt to capture the collective definition of body and identity beyond the Foucauldian framework invites further development of her theory. In order to elucidate Butler's position and remove some shortcomings in her work exposed by her critics, I present a sociological reconstruction of her theory of gender and the body in terms of the performative theory of social institutions (mainly developed by Barry Barnes and David Bloor) and the notion of artificial kind (developed by Martin Kusch). In order to complement and critically evaluate the theoretical reconstruction, as well as to generate new ideas within the theoretical framework, I have conducted qualitative empirical research on transsexual people. The study uses transsexuals as informants of common sense knowledge concerning sex and gender. The study is comparative in that it is based on fieldwork in Scotland and Catalonia. According to my reconstruction, the Heterosexual Matrix is a folk theory about sex and gender and a social institution. Put differently, the Matrix is a body of collectively defined knowledge categories and practices; these practices have a circular, self-validating and self-referential structure; they involve the mastery of a language; and they regulate the normative standards of acceptable identities. Moreover, the Matrix's coherence is protected by collective sanctioning of deviant behaviour. The consensus regarding its basic categories is sustained through the reflexive monitoring of gender identity. I argue that Butler's notion of citationality can be reconstructed as a contingent case-by-case application of norms and categories. The possibility of subversion is an inevitable byproduct of such contingency. I reconstruct the Matrix as a self-fulfilling prophecy that validates itself by shaping bodies, desires and identities according to its laws. Put differently, the category of 'sex' is not simply descriptive of a pre-existing biological reality, or natural kind; instead it constitutes the body and our conceptions of it. The qualitative data gathered from in-depth interviews with transsexual people, including a cross-cultural comparison between Spain and the UK, reveal the circularity and self-referentiality of the Matrix terms both in expert and in folk discourse. The empirical case study demonstrates the existence of gender myths that are cited as standards of normative identities. It also identifies the ways in which sanctions protect meaning stability. Transsexuals' accounts and practices corroborate the importance of gender as surface performance and substantiate the view that repetitive citation of the Matrix categories performs the body as an artificial kind. Moreover, the cross-cultural comparison demonstrates the conventionality of the Matrix. In sum, the case study confirms the theoretical reconstruction of the Heterosexual Matrix as a conventional, performative, collectively defined and self-referential social institution, and supports its conceptualisation as a self-fulfilling prophecy.
Keywords: Sociology; Gender; Sexuality